Dialectics Of Traditional Pesantren Education System In the era of society 5.0 - Hirzulloh, Muhammad Faiq (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the relevance of the traditional pesantren education system in the era of society 5.0. This research uses a qualitative approach and uses description as a form of research. Data analysis was conducted interactively. Data sources include a number of books and scientific journal articles that discuss various efforts to enhance the role of pesantren in empowering Indonesian Muslims in the era of society 5.0. The results obtained in the research show that the Daarul Ahkaam Islamic boarding school as an Islamic educational institution has many goals, roles, and functions in the community. In addition, the Daarul Ahkaam Islamic boarding school as an educational institution is essential for the empowerment of Muslims in Indonesia through Islamic boarding schools as an Islamic Education institution through its existence making them able to survive the changes and dynamics of life that occur in the era of Society 5.0 with the understanding and practice of Islamic religious knowledge, development of religious character, development of spiritual intelligence modernization of the education system and the formation of Islamic scholars. This research has an important aspect that pesantren is an Islamic educational institution with several characteristics, namely mosques, pondok, kyai, ustad, santri, and kitab kuning learning.Â